DARK ADAPTATION IN MACULAR TELANGIECTASIA TYPE 2. Issue 10 (October 2020) - Tzaridis, Simone; Hess, Kristina; Heeren, Tjebo F. C.; Nadal, Jennifer; Mai, Clarissa; Herrmann, Philipp; Charbel Issa, Peter; Holz, Frank G.
Abstract : Purpose: To evaluate dark adaptation (DA) in patients with macular telangiectasia Type 2 (MacTel). Methods: After a local photobleach (4 × 4° size, 83% bleach), DA was measured using a test stimulus (2° diameter) projected at 5° eccentricity horizontal from the foveal center within the temporal parafovea. Cone plateau, rod intercept time, and rod recovery rate (S2) were calculated from the resulting DA curves. Findings were correlated with disease stages (according to Gass and Blodi), the area of ellipsoid zone loss in optical coherence tomography, and macular pigment loss ("MP-Classes 1–3"). Results: Fifty-nine eyes of 59 patients were compared with 18 eyes of 18 healthy controls. Dark adaptation was significantly impaired in patients with MacTel. Although differences were most pronounced for parameters indicating rod-mediated recovery, cone-mediated recovery was also decreased, yet to a lesser extent. Dark adaptation parameters were only weakly associated with disease stages and ellipsoid zone loss. A better association was found between rod-mediated recovery (S2 and rod intercept time) and macular pigment loss (Kendall's tau for rod intercept time: 0.69 and S2: −0.51; both P < 0.0001). Conclusion: Dark adaptation is significantly impaired in patients with MacTel. Our results indicate an association of reduced macular pigment and rod dysfunction in MacTel. Abstract : Supplemental Digital Content is Available in the Text.Dark adaptation is significantly impaired in patients with macular telangiectasia Type 2 (MacTel). Reduced rod-mediated recovery was found to be associated with the depletion of macular pigment, which is a pathognomonic finding in MacTel. These findings may further contribute to our understanding of pathophysiological changes in MacTel.